Implementation of training and development program to improve customers’ satisfaction at Beximco Pharmaceuticals Ltd. - Tabassum, Anika (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.